1987
DOI: 10.1149/1.2100463
|View full text |Cite
|
Sign up to set email alerts
|

The Catalysis of the Oxygen Evolution Reaction by Iron Impurities in Thin Film Nickel Oxide Electrodes

Abstract: The effects of iron coprecipitated into thin film nickel oxide electrodes or introduced in the 25 weight percent KOH electrolyte were studied by a combination of galvanostatic and open-circuit decay methods. Effects on voltammetric behavior and on the oxygen overpotential were observed in thin film electrodes with as little as 0.01% iron present. The overpotential was further lowered by 1% iron to the extent that the nickel oxide charge storage reaction was adversely affected. Higher concentrations of iron cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

79
924
5
7

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 880 publications
(1,015 citation statements)
references
References 31 publications
79
924
5
7
Order By: Relevance
“…The Tafel slopes reported in the literature 7-9,18 cover a lower current density range and widely different values can be found. Two papers 8,9 also report large variations in Tafel slope with the composition of NiFe(OH) 2 which we did not observe. We believe that our values are more reliable since the microelectrode technique employed provides a very low uncompensated ohmic drop between working and reference electrodes.…”
Section: Resultscontrasting
confidence: 74%
“…The Tafel slopes reported in the literature 7-9,18 cover a lower current density range and widely different values can be found. Two papers 8,9 also report large variations in Tafel slope with the composition of NiFe(OH) 2 which we did not observe. We believe that our values are more reliable since the microelectrode technique employed provides a very low uncompensated ohmic drop between working and reference electrodes.…”
Section: Resultscontrasting
confidence: 74%
“…Mixed transition metal oxides usually show superior OER activity compared to either of the parent metal oxides. It was reported that Ni doping in Co oxides could lead to the creation of new active sites with lower activation energy 32,33 , and Fe dopants were found to enhance the OER activities of Ni hydroxides or oxides 11,[34][35][36][37] . Recently, an excellent OER performance was observed on amorphous NiCoFe oxides, which were prepared by a photochemical route 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of electrodeposited amorphous α-Ni(OH)2 and its ageing to β-Ni(OH)2 in basic electrolytes suggested that oxygen evolution occurred at lower onset potential for β-Ni(OH)2/β-Ni(O)OH. 18,[21][22][23][24][25][26][27][28] Yachandra and Nocera challenged this notion by correlating structure to activity in a nickel-borate oxygen evolution catalyst. 29 Dai established that crystalline Fe-doped α-Ni(OH)2 on carbon nanotubes is more active than the equivalent β-phase material.…”
Section: Raman Spectramentioning
confidence: 99%